Development and Characterization of Bio-Polymer Electrolyte iota-carrageenan with Ammonium Salt for: Electrochemical Application. (2019) - Moniha, V.; Alagar, M.; Selvasekarapandian, S.; Sundaresan, B.; Hemalatha, R.
Abstract: Bio- polymer electrolytes based on iota- carrageenan with ammonium formate (NH4 HCO2 ) in different concentrations have been prepared by solution casting technique. FTIR analysis confirms the complex formation between the polymer and salt. The highest conductivity at ambient temperature has been found to be 1.11×10 -3 S/cm for iota- carrageenan with NH4 HCO2 (0.4 wt %) using AC impedance analysis. The activation energy of the prepared polymer electrolytes have been calculated from the Arrhenius plot. The highest ionic conducting polymer electrolyte iota- carrageenan with NH4 HCO2 (0.4 wt %) has low activation energy 0.34 eV. The transference number has been measured by the dc polarization method. The result reveals that the conducting species are predominantly due to ions. Using the highest conducting polymer electrolyte, a proton battery has been fabricated and cell parameters have been reported.